2006
DOI: 10.3171/foc.2006.20.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Focal cortical dysplasia: a review of pathological features, genetics, and surgical outcome

Abstract: Focal cortical dysplasia (FCD) is found in approximately one-half of patients with medically refractory epilepsy. These lesions may involve only mild disorganization of the cortex, but they may also contain abnormal neuronal elements such as balloon cells. Advances in neuroimaging have allowed better identification of these lesions, and thus more patients have become surgical candidates. Molecular biology techniques have been used to explore the genetics and pathophysiological characteristics of FCD. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 53 publications
(76 reference statements)
0
22
0
2
Order By: Relevance
“…In patients with histologically proven FCD of Taylor's balloon cell type, a mutational analysis of the TSC1 gene has been described which indicates a pathogenic relationship to TSC [21]. Another concept of a possible genetic pathway assumes subtle polymorphism mutations in the regulatory ele- of single genes or, alternatively, involvement of multiple genes [22]. Further genetic investigations are required in familial occurrence of FCD.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with histologically proven FCD of Taylor's balloon cell type, a mutational analysis of the TSC1 gene has been described which indicates a pathogenic relationship to TSC [21]. Another concept of a possible genetic pathway assumes subtle polymorphism mutations in the regulatory ele- of single genes or, alternatively, involvement of multiple genes [22]. Further genetic investigations are required in familial occurrence of FCD.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the lesion may be clinically silent, only discovered at autopsy, or there may be some form of cognitive impairment but no epilepsy (Palmini et al 2004;Wang et al 2006). In epilepsy samples, although the numbers vary due to the described heterogeneity in definitions, as well as research sampling biases and other factors, FCD is identified in as many as one quarter of patients with focal seizures (Kuzniecky et al 1993).…”
Section: Malformations Of Cortical Development (Mcd)mentioning
confidence: 97%
“…32 The authors of a study that included adult patients demonstrated a mean epilepsy duration of 21 years, with mean age at surgery of 28 years. 53 In their surgical series, Wang et al 63 showed an overall postoperative seizure freedom or reduction in frequency rate of Ն 70% in 58% (range 33-89%) of their patients with FCD. In 2 long-term prospective studies, the rate of seizure freedom was Ͻ 50%, which suggests an overall decline in the rate of long-term seizure control.…”
Section: Seizure Outcome After Surgerymentioning
confidence: 98%